The lexical framework of contemporary archaeology – systematizing concepts, terms, research approaches, and knowledge of the past: Observations made when reading book entitled Leksykon terminów archeologicznych - Drewicz, Mateusz (Folia Praehistorica Posnaniensia, 2025)
The article explores the significance, guiding principles, and structure of Leksykon terminów archeologicznych, offering a critical assessment of the publication in light of the current needs and challenges facing Polish archaeology. The lexicon is examined in relation to other frameworks for structuring disciplinary knowledge within the field. This systematized publication, edited by Arkadiusz Marciniak, Anna I. Zalewska, Dorota Cyngot, Stanisław Iwaniszewski, Hanna Kowalewska-Marszałek, and Franciszek M. Stępniowski, published in 2024, presents a conceptualization of the archaeological research process rooted in the Polish research tradition. The article highlights the lexicon’s distinctive contribution as both an extension of prior efforts toward conceptualization of Polish archaeology and a point of departure for further discussion on establishing systematic lexical framework of contemporary Polish archaeology.